PERBANDINGAN KINERJA KEUANGAN BANK UMUM KONVENSIONAL DAN BANK UMUM SYARIAH PERIODE 2015 – 2019 - Sthepanie Rizky Rianti *; Puji Hadiyati (Perbanas Institute, 2021)
The purpose of this research to analyze the comparison of the financial performance of Islamic Commercial Banks and Conventional Commercial Banks for the period 2015 - 2019. The population in this study took from conventional commercial banks and Islamic commercial banks. The samples use in this research are thirteen conventional commercial banks and four Islamic commercial banks period 2015-2019. The sampling period is 5 years with the period 2015 to 2019. The variables used are financial ratios which include Capital Adequacy Ratio (CAR), Non Performing Loans (NPL), Return on Assets (ROA), Operating Expense Ratio (OER), and Loan to Deposit Ratio (LDR). The data analysis technique in this study used descriptive statistical analysis, normality test and two-difference test analysis (Independent Sample t-test). The test results show that the CAR, ROA, BOPO, and LDR/FDR variables have a significant difference between Conventional Commercial Banks and Islamic Commercial Banks, while for the NPL/NPF variables there is no significant difference between Conventional Commercial Banks and Islamic Commercial Banks.